Students' Perception About Powerpoint Used by the Teacher as a Teaching Media in English Language Teaching and Learning - Febri Aini; Syafryadin Syafryadin (Jadila: Journal of Development and Innovation in Language and Literature Education, 2023)
Education is very important the frist one is for every child to have as the next generation of the nation. The development of ICT is currently having a major impact on human life in any aspect, one of which is in the aspect of education. One of the conveniences and sophistication of current ICT developments is the availability of many tools or applications that educators can use as learning media. Powerpoint is a tool that is currently widely used by teachers to support learning. This research aims to find out what are the students' perceptions about the use of powerpoint by English teachers as a teaching media. The method used in this study is a quantitative method. The sample of this study was 30 students from SMAIT IQRA Kota Bengkulu who were taken randomly. The research instrument used was a questionnaire. In analyzing the data, the study used descriptive analysis. Basd on the results, it is shows that the use of powerpoint media in english teaching and learning is fearlu good for the students with percentage responses of 57%. It can be concluded that the use of PowerPoint media by teachers in the process of teaching and learning English at SMAIT IQRA Kota Bengkulu is quite good. Teachers can innovate and be even more creative in making material for making the learning English with this media is better and maximal, especially for students.